Financial integration and investment diversification benefits in East Asia and Pacific - Li, Cong (2017)
With economic globalization, countries all over the world pay more attention to financial integration for further development opportunities. The paper describes how East Asia and Pacific (EAP) region is integrated financially in recent years. Several measurements of the degree of financial integration are used for EAP region during the period from 1990 to 2017. Involved two crises in this period, stock market indices are investigated in five time periods to show changes of financial integration. Additionally, in integrated markets, investment diversification generates benefits for investors. The paper estimates diversification benefits for investors in China and concludes the impact of financial integration on financial markets and the relationship between financial integration and diversification benefits.